2015
DOI: 10.1007/s00423-015-1339-2
|View full text |Cite
|
Sign up to set email alerts
|

Closure method for thick pancreas stump after distal pancreatectomy: soft coagulation and polyglycolic acid felt with fibrin glue

Abstract: Our novel pancreatic stump closure method appears to be simple and effective, particularly in patients with thick pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…The incidence of clinically significant POPF (Grade B, C) was 13.3%. POPF rates don’t deviate significantly from DISPACT trial (stapler 32% vs. hand sewn 28%) [ 7 ] and other LDP data [ 20 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of clinically significant POPF (Grade B, C) was 13.3%. POPF rates don’t deviate significantly from DISPACT trial (stapler 32% vs. hand sewn 28%) [ 7 ] and other LDP data [ 20 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most favored and reported techniques are stapler closure vs. hand-sewn closure of the pancreatic remnant. It also includes laparoscopic approaches, radiofrequency-assisted dissection procedure, and biological glue [ 22 , 23 ]. Systematic reviews [ 6 , 8 ] and randomized study [ 7 ] showed that there were no significant differences between stapler closure and hand-sewn closure in POPF.…”
Section: Discussionmentioning
confidence: 99%
“…POPF is a life-threatening complication that significantly prolongs hospital stay and increases healthcare costs 17 . Substantial effort has been made to prevent pancreatic fistula, such as modifying the surgical procedure and drainage regime, and selecting materials that can minimize the occurrence of POPF 3 5 , 18 , 19 ; however, a definitive approach for preventing POPF is still lacking 6 , 7 . Non-resorbable adhesives such as neoprene or prolamine are commonly used in clinical practice to prevent the leakage of pancreatic juice; however, they are limited in that permanent closure can cause pancreatic atrophy and complete loss of exocrine function 20 .…”
Section: Discussionmentioning
confidence: 99%
“…While mortality rates from pancreatic surgery have been declining due to improvements in surgical intervention and medical technology, pancreatic fistula still occurs at a high rate of 10–40% 2 . There are several techniques for preventing leakage of pancreatic secretions, including handsewn sutures, staples 3 , or surgical adhesive materials 4 , 5 . Several materials including fibrin glue and polyglycolic acid felt are widely used in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…POPF can be triggered by serious incidents such as intra-abdominal abscess and intra-abdominal arterial bleeding and it can be fatal. To prevent POPF, several techniques including hand-sewn closure [ 8 10 ], stapled closure [ 2 , 3 , 8 , 11 , 12 ], main pancreatic duct ligation [ 8 , 10 ], bipolar scissors [ 13 ], the application of fibrin glue [ 14 , 15 ], pancreaticoenteric anastomosis [ 9 , 16 , 17 ], mesh reinforcement of pancreatic transection [ 18 20 ], TachoSil ® patches [ 21 ], Teres ligament patch [ 22 ] have been reported. Although the superiority of stapler closure is not clear compared to the other techniques [ 3 , 8 , 12 ], the simple and easy stapler closure method is recently becoming one of the commonly performed techniques.…”
Section: Introductionmentioning
confidence: 99%